Methods of Developing Expressive Reading in Elementary School Students - Nasirova Nazokat Najimovna (Web of Journals Publishing, 2023)
As we all know; the elementary school level is the foundation of the education system. Because almost all the student’s abilities begin to appear and develop in that period. Some students begin to write poems, some begin to prove that they are the owners of beautiful speech, some draw very beautifully. At that time, the responsibility of the teacher becomes strong, it is necessary to create conditions for students according to their abilities. In this article, we will discuss some expressive reading tips and techniques available in each language to help develop those beautiful speakers and their importance in child speech.
Keywords: expressive reading, method, speech, syllable, word, pronunciation